Direct Synthesis of ESBO Derivatives-18O Labelled with Dioxirane. (12th September 2013) - La Tegola, Stefano; Annese, Cosimo; Suman, Michele; Tommasi, Immacolata; Fusco, Caterina; D'Accolti, Lucia
Abstract : This work addresses a new approach developed in our laboratory, consisting in the application of isolated dimethyldioxirane (DDO, 1a ) labelled with 18 O for synthesis of epoxidized glyceryl linoleate (Gly-LLL, 2 ). We expect that this work could contribute in improving analytical methods for the determination of epoxidized soybean oil (ESBO) in complex food matrices by adopting an 18 O-labelled-epoxidized triacylglycerol as an internal standard.